Penerapan Program Literasi di SMP Negeri 2 Ambon Tahun Pelajaran 2018/2019 - Aldy Buton; Amjad Salong; William George Mozes Louhenapessy (Universitas Pattimura, 2025)
Literacy skills form an essential foundation in modern education, yet Indonesian students’ literacy levels still require improvement. This study aims to analyze the process of implementing the literacy program at SMP Negeri 2 Ambon in the 2018/2019 academic year and its impact on students' reading interest. The research utilized a descriptive quantitative method, collecting data through observation, interviews, questionnaires, and documentation with class VII8 students as the main sample. The results indicate that the literacy program, through the habit of reading for 15 minutes before lessons, was conducted regularly and effectively enhanced students’ interest in reading. Supporting facilities such as the library, reading corners, and the involvement of teachers and parents further strengthened these positive outcomes. The findings demonstrate that the program’s implementation successfully cultivated a strong reading culture and met the standards for school literacy activities. The implication is the need to strengthen collaboration among schools, parents, and the community, as well as to expand reading materials and provide ongoing literacy training to sustain the program’s success.